2023
DOI: 10.54434/candj.165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutraceuticals in the Prevention and/or Treatment of COVID-19: An Umbrella Review

Randa Karzon,
Andrew Jackson,
Iva Lloyd
et al.

Abstract: Background: To identify the results of published review literature regarding nutraceuticals, including probiotics, melatonin, poly-unsaturated fatty acids (PUFAs), quercetin, N-acetyl cysteine (NAC), and propolis as they relate to the prevention and/ or treatment of COVID-19 (CV) and/or long COVID (long CV) and to outline key areas to consider for clinical application and for further research. Methods: This paper is part of a six-part umbrella review which progresses from a living review. This review incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The Task Force identified and produced six umbrella reviews encompassing herbal medicine 11 ; vitamins 12 ; minerals 13 ; nutraceuticals (quercetin, n-acetyl cysteine, omega-3 fish oil, melatonin, probiotics, and propolis) 14 ; diet and food 15 ; and movement, exercise and breathing. 16 As outlined in Table 1, the umbrella review started with 94 narrative reviews and 308 systematic reviews identified by the live review.…”
Section: Included Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Task Force identified and produced six umbrella reviews encompassing herbal medicine 11 ; vitamins 12 ; minerals 13 ; nutraceuticals (quercetin, n-acetyl cysteine, omega-3 fish oil, melatonin, probiotics, and propolis) 14 ; diet and food 15 ; and movement, exercise and breathing. 16 As outlined in Table 1, the umbrella review started with 94 narrative reviews and 308 systematic reviews identified by the live review.…”
Section: Included Reviewsmentioning
confidence: 99%
“…Oakes et al11 reviewed the publications investigating herbal medicine and found therapeutic interventions that combined herbal medicines with conventional Western medical treatments showed significant improvements in both ROR and ROC. Although additional research is needed with respect to nutraceuticals, according to Karzon et al,14 the current data suggests that the anti-inflammatory, anti-microbial, and antioxidant properties of various NHPs provided therapeutic value both preventively and in treatment of COVID-19. There are also a number of therapies which were reviewed by Carter et al,16 such as breathing exercises, physical exercise, and mind-body exercises that are showing promise both from a preventive perspective and from a treatment perspective of COVID-19 due to their direct impacts on health and their indirect ability to modulate the immune system by decreasing stress.…”
mentioning
confidence: 91%